Contact and Compromise: Explaining Support for Conciliatory Measures in the Context of Violent Intergroup Conflict. (August 2014) - Pickett, Justin T.; Baker, Thomas; Metcalfe, Christi; Gertz, Marc; Bellandi, Rose
Objectives: Informed by intergroup contact theory, this study explores the relationships between intergroup contact, perceived out-group threat, and support for conciliatory solutions to the violent conflict between Israeli Jews and Palestinians in Israel and the Palestinian territories. Methods: Regression and structural equation models analyze public opinion data collected in Israel in 2011 and 2012. The analyses assess whether quantity and quality of Israeli Jews' contact with Israeli Arabs in day-to-day encounters are associated with their support for conciliatory policies. Results: The quality, but not the quantity, of contact is associated with lower levels of perceived Palestinian threat and, in turn, with increased support for compromise. Conclusion: The current study provides initial evidence that everyday interactions with Israeli Arabs, when they occur under optimal conditions, may have the potential to reduce Israeli Jews' perceptions of Palestinian threat and, in turn, increase their support for compromise.